Peculiarities of the relationship between the terminal site of glycolysis and the initial segment of gluconeogenesis in the myocardium and skeletal muscles of animals irradiated at different doses - Stepanov, G.; Vastyanov, R.; Kostina, A.; Mokriienko, E. (Journal of Education, Health and Sport, 2023)
Existing types of muscles differ not only structurally, but also metabolically (direction of energy exchange, choice of biosubstrates, dependence on the action of mediators, hormones, etc.). A number of studies have been devoted to the study of the impact of ionizing radiation on metabolism in muscle tissue. After irradiation, thickened muscle cells with enlarged nuclei appear in the heart muscle, the number of which does not decrease for 6 months, which indicates a violation of nuclear-cytoplasmic relations in myocardial cells. Phosphoenolpyruvate carboxykinase which ensures the utilization of cytoplasmic oxaloacetate and its transformation into phosphoenolpyruvate, completes the initial stage of gluconeogenesis and can limit the rate of gluconeogenesis from lactate. It should be emphasized that phosphoenolpyruvate carboxykinase is more active in skeletal muscles, where the activity of pyruvate kinase and lactate dehydrogenase is increased. The purpose of the work is to investigate the peculiarities of the relationship between the terminal site of glycolysis and the initial segment of gluconeogenesis in the myocardium and skeletal muscles of animals irradiated at different doses. The authors proved that in animals irradiated at a dose of 0.5 Gy, the activity of pyruvate kinase in the myocardium and skeletal muscle increases compared to intact animals. In the blood, on the contrary, there is a decrease in the activity of this enzyme compared to intact animals. When animals are irradiated at a dose of 1.0 Gy, diametrically opposite changes are observed. When animals are irradiated at a dose of 0.5 Gy, there is a slight decrease in the activity of lactate dehydrogenase in the myocardium and blood against the background of an increase in the activity of this enzyme in skeletal muscle. Irradiation of animals at a dose of 1.0 Gy leads to an acute increase in lactate dehydrogenase activity in the myocardium and skeletal muscle. The data obtained revealed that in animals irradiated at a dose of 0.5 Gy, the activity of phosphoenolpyruvate carboxykinase in skeletal muscle increases, while in cardiac muscle, on the contrary, its activity decreases as well as in blood. With an increase in the radiation dose to 1.0 Gy, diametrically opposite changes in the activity of phosphoenolpyruvate carboxykinase are observed. The authors concluded that outlined changes in the waу of intramuscular glycolysis and gluconeogenesis reactions show the pathophysiologcal mechanisms of biochemical supply restructuring as the result of ionizing irradiation influence. From the fundamental point of view these results show the direction of pathophysiologically oriented pharmacological correction of radiation-provoked muscle disturbances.